Implementasi Pembelajaran dengan Pendekatan BrainBased Learning terhadap Kemampuan Koneksi Matematis Siswa - Yuli Sahara; Uba Umbara (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
The purpose of this is to know the ability of mathematical connections ofstudents in learning mathematics with mathematical connections ability of studentsusing Brain-Based Learning.The population in this study are students of SMPN 2Kadugede, while the sample in this study were students of grade VII SMPN 2Kadugede. Sampling technique in this research use purposive sampling, in twoclasses to determine experiment class and control class.The experimental classreceive the learning by using the Brain-based Learning approach, while the controlclass receive the learning by using Direct Intruction approach.The research instrumentthat is test sheets of 6 problem description form. From the test result of mathematicalconnection ability of students obtained the average of initial test of the experimentalclass is 2.96 and the control class average is 3.75. While in the final test the averageexperiment class is 26.08 and the control class is 11.05.The data analysis techniqueuses the t-test to test the statistical hypothesis. From the this calculation obtained thetvalue of calculated equality test of two averages of 1.02 then on the ttable at 5%significance level and degrees of freedom 49, obtained table value 2.011 because -2.011 <1.02 <2.011 then H0 is accepted, meaning no difference between The initialtest grade of the experimental class and the control class.While at two difference oftwo average obtained t value 8,23 then at ttabel at 5% significance level and degree offreedom 46 obtained value ttable 2.011 because 2,011> 8,23 then H1 accepted, thatmean ability mathematical connection of student which use approach of Brain-basedLearning is better than the mathematical connection ability of students using DirectIntruction learning. There is an increase of students' mathematical connection abilitywith Brain-Based Learning approach that is in medium category and student'sresponse to learning using Brain Based Learning approach shows positive response.